Thermal Conductivity Variation with Temperature for Lead-Free Ternary Eutectic Solders - Aksoz, Namik; Ozturk, Esra; Bayram, Umit; Aksoz, Sezen; Kervan, Selcuk; Ulgen, Ahmet; Marasli, Necmettin (SPRINGER, 2013)
The variations of the thermal conductivity with temperature for the lead-free ternary eutectic solders Bi-42.73 wt.%Sn-1.03 wt.%Ag (Bi-Sn-Ag), Sn-3.5 wt.%Ag-0.9 wt.%Cu (Sn-Ag-Cu), Sn-6 wt.%Sb-5 wt.%Ag (Sn-Sb-Ag), Sn-42.8 wt.%Bi-0.04 wt.%Cu (Sn-Bi-Cu), and In-48.4 wt.%Sn-2.31 wt.%Ag (In-Sn-Ag) were measured using a linear heat flow apparatus. It was observed that the thermal conductivities of solid phases for the Bi-Sn-Ag, Sn-Ag-Cu, Sn-Sb-Ag, Sn-Bi-Cu, and In-Sn-Ag solders decrease linearly with increasing temperature. The thermal conductivities of the Bi-Sn-Ag, Sn-Ag-Cu, Sn-Sb-Ag, Sn-Bi-Cu, and In-Sn-Ag solders at their melting temperature were obtained as 17.89 +/- A 1.6 W/K-m, 49.89 +/- A 4.5 W/K-m, 41.96 +/- A 3.8 W/K-m, 20.03 +/- A 1.8 W/K-m, and 70.21 +/- A 6.3 W/K-m, respectively. The thermal temperature coefficients for the Bi-Sn-Ag, Sn-Ag-Cu, Sn-Sb-Ag, Sn-Bi-Cu, and In-Sn-Ag solders were also determined to be -2.894 x 10(-3) K-1, -0.907 x 10(-3) K-1, -1.246 x 10(-3) K-1, -2.638 x 10(-3) K-1, and -1.250 x 10(-3) K-1, respectively, from plots of thermal conductivity versus temperature.
Keywords: Metals; thermal conductivity; thermal temperature coefficient; lead-free solders; PB-SN ALLOYS; ELECTRICAL CONDUCTIVITIES; INTERFACIAL ENERGIES; PURE METALS; SOLIDIFICATION; LIQUID; Engineering; Materials Science; Physics